2022
DOI: 10.1177/09564624221076289
|View full text |Cite
|
Sign up to set email alerts
|

Use of ixekizumab in an HIV-positive patient with psoriatic arthritis

Abstract: Psoriasis is a chronic immune-mediated disease of the skin. The incidence of psoriasis among people living with HIV (PLHIV) is higher than that in the general population. The mechanism is complex, the manifestations are varied, and the treatment is difficult. Biotherapy has greatly alleviated psoriasis, but clinical trials often exclude PLHIV, and evidence is limited to case reports. Here, we report a man living with psoriatic arthritis who had poor response to traditional treatments. After receiving the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The American Academy of Dermatology and National Psoriasis Foundation (AAD-NPF) guidelines recommend the use of anti-IL-17 monoclonal antibodies in HIV patients who have been receiving antiretroviral therapy and have a well-controlled viral load [ 44 ]. Specifically, with regard to IL-17 inhibitors, there are several case reports in the literature showing that these are an effective and safe therapeutic option for the treatment of psoriasis in HIV+ patients [ 74 , 75 ]. Similarly, data on the use of IL-23 inhibitors in HIV+ patients are reassuring.…”
Section: Resultsmentioning
confidence: 99%
“…The American Academy of Dermatology and National Psoriasis Foundation (AAD-NPF) guidelines recommend the use of anti-IL-17 monoclonal antibodies in HIV patients who have been receiving antiretroviral therapy and have a well-controlled viral load [ 44 ]. Specifically, with regard to IL-17 inhibitors, there are several case reports in the literature showing that these are an effective and safe therapeutic option for the treatment of psoriasis in HIV+ patients [ 74 , 75 ]. Similarly, data on the use of IL-23 inhibitors in HIV+ patients are reassuring.…”
Section: Resultsmentioning
confidence: 99%
“…9 A few case reports have demonstrated that anti-IL-17 are a safe option for treating psoriasis and psoriatic arthritis in PLHIV. 10,11 Real-life studies on IL-23 inhibitors have also included patients with concomitant chronic infections, including HIV, showing no adverse events throughout the treatment period. [12][13][14] Additionally, two case reports of patients treated with IL-23 inhibitors during chronic HIV infection have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%